Faktor Risiko Kejadian Diare Pada Anak Di Puskesmas Toapaya, Toapaya Asri, Kabupaten Bintan, Kepulauan Riau - Yola Mia Jayanti; Dyah Suryani (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2021)
Background: Diarrhea is one of the major causes of morbidity and mortality around the world anddevelop countries. In 2014, there were 86 cases of diarrhea in Toapaya Asri District and 34 of themwere toddlers. Most of the people already have their own latrines, yet there are still toddlers excrete onimproper excretion places. There are also some families who are not having their own excretion facilitiesin their houses. The lack of knowledge toward individual cleanliness such as the mothers and toddlershard willingness to wash the hands is also related. The objective of this research is to discover the riskfactors of diarrhea incidence to toddlers at Toapaya primary health care in Toapaya Asri VillageRegency of Bintan Province of Riau Island.Method: This quantitative research used cross sectional study design by 71 respondents of toddlersamples. The primary data in this research were obtained by conducting interviews, observations,questionnaires, and check list. Findings: The relation of toddlers’ excretion behavior and the diarrheaincidence are in P-value 0,002; latrines ownership and the diarrhea incidence are in P-value 0,008.Meanwhile, the variable of mothers’ hand-washing habit has no relation toward the diarrhea incidencefrom its P-value 1,000; and the variable of toddlers’ handwashing habit has no relation toward thediarrhea incidence from its P-value 0,756.Conclusion : This research shows that the excretion behavior of toddlers and the ownership of latrinesrelate the diarrhea incidence to toddlers. On the other hand, mothers’ and toddlers’ hand-washing habithas no relation toward the diarrhea incidence.Key Words: Diarrhea, Latrines’ Ownership, Cross Sectional